Resuscitated sudden cardiac death due to severe hypokalemia caused by teff grain herbal tea: A case report - Murat Akçay; Serkan Yüksel (Türk Kardiyoloji Derneği Arşivi, 2020)
Obesity is a common health problem and the prevalence is increasing worldwide. The improper and unregulated use of unconventional therapies, especially herbal treatment methods, has grown due to widespread availability. In our case, a 41-year-old male patient developed palpitation, confusion, loss of consciousness, and cardiac arrest while at home. An emergency medical team was called and chest compressions were performed by his wife until the medical team arrived. Ventricular fibrillation was detected on the monitor 5 minutes after the cardiac arrest occurred and the patient was defibrillated. A physical evaluation revealed hypotension and tachycardia. Electrocardiography (ECG) showed a fast idioventricular rhythm with capture and fusion beats and evident J waves in leads DII, DIII, and aVF. Brain magnetic resonance imaging and thoracic tomography revealed no pathology to explain his clinical condition and the coronary angiography results were not significant. The laboratory parameters included potassium (K): 2.23 mEq/L, ionized K (arterial blood): 2.43 mEq/L, sodium: 142 mEq/L, calcium: 9.3 mg/dL, creatinine: 1.6 mg/dL, pH: 7.29, cardiac troponin I: 0.12 (normal range: 0–0.11 ng/mL) and creatinine kinase mass: 8.3 (normal range: 0–3.23 ng/mL). After fluids and electrolyte replacement therapy were administered, the ECG results revealed narrow QRS complex atrial fibrillation followed by a normal sinus rhythm with a 490 ms corrected QT interval. The patient was extubated in follow-up. There were no risk factors for coronary artery disease, no history of drug or other substance use, and no exposure to excessive emotional or physical stress. The patient said that he had been consuming a large quantity of teff tea for 5 days to lose weight. He was discharged without any complications and has been asymptomatic in 9 months of follow-up. The inappropriate use of weight loss alternatives, especially herbal therapies such as teff tea, and the incidence of associated side effects are increasing due to wide availability and easy access. The general population should be warned about this issue.